Zoom in, zoom out: A shift-share analysis of productivity in Switzerland based on micro data - Benjamin Tissot-Daguette; Jean-Marie Grether (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
Using novel data on value added in Switzerland we propose to use a growth rate decomposition technique, in the spirit of shift-share analysis, to analyze the patterns of regional competitiveness over the 2011-2015 period. The growth differential of a region (or canton) depends on four terms, three structural effects and one competitive effect. The competitive effect turns out to be the dominant force at a high level of aggregation. An interesting pattern of structural effects unveils when working at a lower level of aggregation, allowing for identification of the leaders and laggers across regions and sectors.
Keywords: R11; R32; 330; firm-level; productivity; shift-share; structural and competitive effects; Switzerland